Chaotic and Hyperchaotic Self-Oscillations of Lambda Diode Composed by Generalized Bipolar Transistors - Jiri Petrzela (Applied Sciences, 2021)
This paper is focused on the investigation of self-oscillation regimes associated with very simple structure of lambda diode. This building block is constructed by using coupled generalized bipolar transistors. In the stage of mathematical modeling, each transistor is considered as two-port described by full admittance matrix with scalar polynomial forward trans-conductance and linear backward trans-conductance. Thorough numerical analysis including routines of dynamical flow quantification indicate the existence of self-excited dense strange attractors. Plots showing first two Lyapunov exponents as functions of adjustable parameters, signal entropy calculated from generated time sequence, sensitivity analysis, and other results are provided in this paper. By the construction of a flow-equivalent chaotic oscillator, robustness and long-time geometrical stability of the generated chaotic attractors is documented by the experimental measurement, namely by showing captured oscilloscope screenshots.